Direct local and global approximation results for operators of gamma type - Karsli, Harun; Özarslan, Mehmet Ali (Hacettepe University, 2010)
In this paper some direct local and global approximation results are obtained for the modified Gamma operators defined by A. Izgi and Büyükyazi?ci? (Approximation and rate of approximation on unbounded intervals, Kastamonu Edu. J. Okt. 11 (2), 451-460, 2003 (in Turkish)), and independently by H. Karsli (Rate of convergence of a new Gamma Type Operator for functions with derivatives of bounded variation, Math. Comput. Modelling 45 (5-6), 617-624, 2007). Furthermore, a Voronoskaya type theorem is given for these operators.
Keywords: Gamma operators; Local and global approximation; Positive linear operators; Voronovskaya type theorem